2015
DOI: 10.2174/0929867322666150209160317
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Mitochondrial Therapeutics for Neurological Disease

Abstract: Neuronal homeostasis is critically dependent on healthy mitochondria. Mutations in mitochondrial DNA (mtDNA), in nuclear-encoded mitochondrial components, and agedependent mitochondrial damage, have all been connected with neurological disorders. These include not only typical mitochondrial syndromes with neurological features such as encephalomyopathy, myoclonic epilepsy, neuropathy and ataxia; but also secondary mitochondrial involvement in neurodegenerative disorders such as Alzheimer's, Parkinson's and Hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 144 publications
0
7
0
Order By: Relevance
“…It is known that mitochondrial biogenesis is affected by several natural compounds (Lai et al 2017), behavioral interventions (Civitarese et al 2007;Guarente 2008;Menshikova et al 2006), and pharmacologic agents (Bar-Am et al 2009;Weinreb et al 2008;Youdim and Buccafusco 2005) that target the mitochondria and have been shown to induce mitochondrial biogenesis and increase ETC activity. Mitochondria-targeted peptides and lipophilic cations may also enhance in vivo delivery of antioxidants or other putative therapeutics (Leitao-Rocha et al 2015). While these interventions have demonstrated efficacy on biogenesis and ETC activity, few studies have examined their associations with mobility in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that mitochondrial biogenesis is affected by several natural compounds (Lai et al 2017), behavioral interventions (Civitarese et al 2007;Guarente 2008;Menshikova et al 2006), and pharmacologic agents (Bar-Am et al 2009;Weinreb et al 2008;Youdim and Buccafusco 2005) that target the mitochondria and have been shown to induce mitochondrial biogenesis and increase ETC activity. Mitochondria-targeted peptides and lipophilic cations may also enhance in vivo delivery of antioxidants or other putative therapeutics (Leitao-Rocha et al 2015). While these interventions have demonstrated efficacy on biogenesis and ETC activity, few studies have examined their associations with mobility in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…One open question is whether striatal and cortical neurons present intrinsic differences in their mitochondrial dynamics profile that may contribute to their differential vulnerability in HD. Concurrently, one notable challenge is to identify pharmacological strategies to counteract excessive mitochondrial fragmentation in HD [4,10].…”
Section: Introductionmentioning
confidence: 99%
“…Neurons are highly sensitive to mitochondrial function as they obtain energy through mitochondrial oxidative phosphorylation. Their dependence and sensitivity requires efficient distribution of mitochondria to maintain distinct mitochondrial morphology and synaptic function [44,45].…”
Section: Mitochondria Quality Control Through Mitophagymentioning
confidence: 99%